2020
DOI: 10.1007/s40264-019-00886-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Safety of the Trastuzumab Biosimilar ABP 980 in Women with HER2-Positive Early Breast Cancer in the Randomized, Double-Blind, Active-Controlled LILAC Study

Abstract: Introduction Although the human epidermal growth factor receptor 2 (HER2) blocker trastuzumab is generally well tolerated, cardiotoxicity can be an important therapeutic limitation. Objective In this prespecified analysis, we compared the cardiac safety of the trastuzumab biosimilar ABP 980 (KAN-JINTI™) and the trastuzumab reference product (RP; Herceptin ®) in the phase III LILAC study (ClinicalTrials.gov identifier NCT01901146). Methods In the neoadjuvant phase of LILAC, after run-in chemotherapy, 725 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…67 Similarly, in another active-controlled, double blind, randomized LILAC study, the cardiac safety of a biosimilar of trastuzumab ABP 980 was put in comparison with Herceptin, a reference product of trastuzumab and the chances of cardiac adverse events were comparatively low. 68 No pharmacokinetic dissimilarity was observed among the immunogenicity and safety characteristics were observed in FDA approved trustuzumab, European Union trastuzumab and biosimilar PF-05280014 and showed consistency with foregoing reports about trastuzumab. 69 In another study, PF-05280014 was compared with the reference trastuzumab-European union in terms of immunogenicity, efficacy and safety which demonstrated non-inferior pharmacokinetics in HER2 þ breast cancer patients receiving the neoadjuvant chemotherapy.…”
Section: Trastuzumabsupporting
confidence: 70%
“…67 Similarly, in another active-controlled, double blind, randomized LILAC study, the cardiac safety of a biosimilar of trastuzumab ABP 980 was put in comparison with Herceptin, a reference product of trastuzumab and the chances of cardiac adverse events were comparatively low. 68 No pharmacokinetic dissimilarity was observed among the immunogenicity and safety characteristics were observed in FDA approved trustuzumab, European Union trastuzumab and biosimilar PF-05280014 and showed consistency with foregoing reports about trastuzumab. 69 In another study, PF-05280014 was compared with the reference trastuzumab-European union in terms of immunogenicity, efficacy and safety which demonstrated non-inferior pharmacokinetics in HER2 þ breast cancer patients receiving the neoadjuvant chemotherapy.…”
Section: Trastuzumabsupporting
confidence: 70%
“…4 ). The overall frequency of cardiac disorders was low throughout the study [ 13 , 15 , 20 ]. The frequency of immunogenicity was found to be low and similar between groups, and no patient tested positive for neutralizing antibodies [ 15 ].…”
Section: Totality Of Evidence For Abp 980: a Brief Reviewmentioning
confidence: 99%
“…EOI event of interest, RP reference product
Fig. 4 Left ventricular ejection fraction in the entire study [ 20 ]. LVEF left ventricular ejection fraction
…”
Section: Totality Of Evidence For Abp 980: a Brief Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…77 Safety analyses showed that there were no clinically significant differences between the biosimilar and reference product. 76-78 Table 5 is a summary of other potential trastuzumab biosimilars currently being investigated. 79-81…”
Section: Trastuzumab Biosimilar In Breast Cancer and Gastric Cancermentioning
confidence: 99%